Analisis Kepribadian Tokoh Utama Film My Idiot Brother 2014 - Riska Patmawati; Rachmalia Gustia Nurhalida; Muhhamad Rangga Prawira Jaelani (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
: This research aims to describe the personality of the main character of the film “My Idiot Brother 2014”, namely Angel, through Sigmund Freud's theory which includes Id, Ego and Superego. This qualitative research uses literary psychology methods. The source of this data was taken from the film “My Idiot Brother in 2014”. The data analysis technique used in this research is descriptive analysis using a literary psychology approach, namely describing the findings. The results of the analysis show that the id is in the form of desires and their fulfillment, the ego includes hateful behavior and the inability to accept reality and finally the superego is conscience awareness of one's bad attitudes and regrets.